Controversies on the network theory of epilepsy: Debates held during the ICTALS 2019 conference - Zaveri, Hitten P; Schelter, Björn; Schevon, Catherine A; Jiruska, Premysl; Jefferys, John G R; Worrell, Gregory; Schulze-Bonhage, Andreas; Joshi, Rasesh B; Jirsa, Viktor; Goodfellow, Marc; Meisel, Christian; Lehnertz, Klaus (Seizure, 2020)
Debates on six controversial topics on the network theory of epilepsy were held during two debate sessions, as part of the International Conference for Technology and Analysis of Seizures, 2019 (ICTALS 2019) convened at the University of Exeter, UK, September 2-5 2019. The debate topics were (1) From pathologic to physiologic: is the epileptic network part of an existing large-scale brain network? (2) Are micro scale recordings pertinent for defining the epileptic network? (3) From seconds to years: do we need all temporal scales to define an epileptic network? (4) Is it necessary to fully define the epileptic network to control it? (5) Is controlling seizures sufficient to control the epileptic network? (6) Does the epileptic network want to be controlled? This article, written by the organizing committee for the debate sessions and the debaters, summarizes the arguments presented during the debates on these six topics.
Keywords: Epilepsy; Edges; Epileptic network; Congresses as Topic; Nodes; nervová síť; epilepsie; Humans; kongresy jako téma; lidé; Nerve Net; Seizure control; Ictogenesis; Epileptogenesis